Genocide: the transformation of a beast - Balla, Evanthia (2017)
Raphael Lemkin invented and presented the idea of genocide, in an analysis of what he called “the Nazi genocide”, in his Axis Rule in Occupied Europe in 1944. Lemkin defined genocide as a broad notion of the violent destruction of a social collectivity. Today, genocide is generally defined as the deliberate and systematic destruction of a group of people, in whole or in part, because of their ethnicity, nationality, religion, or race. Definition first set out in article II of the 1948 Convention on the Prevention and Punishment of Genocide1 . Although the term was invented in 1944, genocide is not a twenty first-century phenomenon; it has been practiced throughout history, since ancient times. The 1948 UN Genocide Convention explicitly refers to its transhistorical character. Indeed, genocide has always been part of human history. What really have changed are the ideologies and cleavages on which genocide is perpetrated. As has been claimed by Martin Swan, different patterns of genocide are broadly synchronized with major historical changes in the international system2 . Thus, the first half of the twentieth century witnessed the climax of inter-imperial conflict in Europe while the period of the Cold War witnessed the decolonization and in its second half the post-colonial states. The post-Cold War period, on the other hand, has been characterised, mainly, by global democratization and international institutional-building. And on this basis, genocide shall be expected to take still further new forms in the future.